Advances in Integrated Soil Fertility Management in sub-Saharan Africa: Challenges and Opportunities - Bationo, Andre; Waswa, Boaz; Kihara, Job; Kimetu, Joseph (Springer Netherlands : Imprint: Springer, 2007)
Food insecurity is a central concern and a fundamental challenge for human welfare and economic growth in Africa. Low agricultural production, results in low incomes, poor nutrition, vulnerability to risks and lack of empowerment. Land degradation and soil fertility depletion are considered the major threats to food security and natural resource conservation in sub-Saharan Africa (SSA). Investments in technology, policy and institutional reforms are needed to increase agricultural productivity to ensure food security and sustained national economies. Past research has generated numerous soil fertility management technologies which if adopted could propel the African continent out of the poverty trap. However, these technologies have had little, if any, impact due to low adoption by the smallholder farmers.